2014
DOI: 10.1248/bpb.13-00744
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of Small RNA Using Lipid Nanoparticles

Abstract: Gene silencing mediated by RNA interference (RNAi) is expected to have a beneficial impact on the treatment of many diseases because of its potency, selectivity and versatility. To maximize the potential of RNAi effectors such as small interfering RNA and microRNA in clinical therapy, the development of a practical delivery system is required, especially for systemic administration. Recent studies demonstrated that chemical modification of these small RNAs and/or encapsulation of them into lipid nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In general, siRNAs have very short half-life, poorly penetrated through the cell membranes, and immediately degraded by RNase in the organism [39]. Therefore, delivery of siRNA molecules with the help of nanocarriers has been proposed as an important strategy that can improve the gene silencing effects [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, siRNAs have very short half-life, poorly penetrated through the cell membranes, and immediately degraded by RNase in the organism [39]. Therefore, delivery of siRNA molecules with the help of nanocarriers has been proposed as an important strategy that can improve the gene silencing effects [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some polymeric nanocarriers, including liposomes, dendrimers, and block copolymers, have been proposed as strong candidates for intracellular delivery of the genetic molecules in order to exert effective gene silencing during cancer treatments and for tissue repair [40][41][42][43]. Furthermore, inorganic and metallic nanoparticles have also been shown to have excellent capabilities for loading and delivery of siRNA molecules to target cells and tissues [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic potential of miRNA-based agents has been investigated in in vivo models of many types of cancers [68][69][70][71][72][73][74] . Systemic delivery methods, such as encapsulation of miRNAs in nanoparticles or chemical modification of miRNAs, could be an effective technique for personalized therapies and cancer treatments [68] .…”
Section: Mirnas In Neuroblastoma Differentiation Therapymentioning
confidence: 99%
“…Systemic delivery methods, such as encapsulation of miRNAs in nanoparticles or chemical modification of miRNAs, could be an effective technique for personalized therapies and cancer treatments [68] . Studies in in vivo neuroblastoma models have also suggested the promise of miRNA-based therapies in treating neuroblastoma [75] .…”
Section: Mirnas In Neuroblastoma Differentiation Therapymentioning
confidence: 99%
“…Both aerosol and systemic delivery have been attempted, depending on the molecular target and if the tumor is metastatized or not. We refer the reader to comprehensive recent reviews [123][124][125], highlighting some work focused on the inhibition of cancer genes. In general, the purpose of gene therapy in lung cancer was to suppress overexpressed carcinogenic pathway, to induce overexpression of wild-type tumor suppressor genes, or it could apply as an immunotherapy.…”
Section: Lung Cancer Gene Therapymentioning
confidence: 99%